Formulasi Pembuatan Sabun Padat Anti Acne Ekstrak Etanol Kulit Pisang Kepok (Musa Balbisiana Colla) - Nur Azizah Syahrana; Indah Indah; Suryanita Suryanita; Muhammad Asri SR (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Herbal soap is a natural soap that can be made from plant extracs. Kepok banana pee (Musa balbiasana colla) as one of the plants that contains high antioxidants is in line with the research objective, namely evaluating the formulation of anti acne solid soap making of kepok banana ethanol extract. This type of research is a laboratory experiment, namely making solid soap from yellow kepok banana peels (Musa balbisiana colla) which is chopped then dried and mashed using a blender then extracted using 70% ethanol and formulated into solid soap preparetions with variations in the concentration of yellow kepok banana extrac FII (10%) and FIII (15%) did not meet the good physical quality for organoleptic testing and 3 people experienced irritation, while FI(5%) met all requirements for good physical quality seen from the organoleptic test, pH 8 test (8-11), the foam strength tes was 6 cm (60mm) and none of the respondents experienced skin irritation. So it can be formulated into solid soap preparations with the best concentration using extract 5%.